2013
DOI: 10.1002/ana.24011
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic prospects for Parkinson disease

Abstract: Dopaminergic therapies such as levodopa have provided benefit for millions of patients with Parkinson's disease (PD) and revolutionized the treatment of this disorder. However patients continue to experience disability despite the best of modern treatment. Dopaminergic and surgical therapies are associated with potentially serious side effects. Non-motor and non-dopaminergic features such as freezing, falling, and dementia are not adequately controlled with available medications and represent the major source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 102 publications
(165 reference statements)
2
96
0
1
Order By: Relevance
“…The discovery of the link between GBA mutations and PD has opened up a novel area for therapeutic investigation, with the possibility of targeting GCase as an important contributor to autophagy dysfunction and alpha synuclein accumulation in the disease [83]. The similarity in clinical presentation, pathology and disease progression between GBA mutation carriers and non-carriers, suggests that neuroprotective treatments developed on the basis of GBA-PD research could be translated to idiopathic PD.…”
Section: Gcase As a Therapeutic Targetmentioning
confidence: 99%
“…The discovery of the link between GBA mutations and PD has opened up a novel area for therapeutic investigation, with the possibility of targeting GCase as an important contributor to autophagy dysfunction and alpha synuclein accumulation in the disease [83]. The similarity in clinical presentation, pathology and disease progression between GBA mutation carriers and non-carriers, suggests that neuroprotective treatments developed on the basis of GBA-PD research could be translated to idiopathic PD.…”
Section: Gcase As a Therapeutic Targetmentioning
confidence: 99%
“…Management of neuropsychiatric and cognitive deficits is an unmet need of the advanced stages of PD [70], with severe impact on daily functioning. The negative effects of DRT on neuropsychiatric and cognitive symptoms in advanced PD stages frequently prevent an optimal therapeutic management.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Parkinson's disease (PD) patient nursing care with those who are assisted in a neurological rehabilitation program can be considered complex work, both from signs and symptoms of the disease itself, as well as the mixed ideas inherent to the principles of rehabilitation (1)(2) . This disorder, which affects about five million people worldwide, was seen for a long time as a mobility disorder, which had the main features of classic motor symptoms resulting from dopamine depletion in specific brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…This disorder, which affects about five million people worldwide, was seen for a long time as a mobility disorder, which had the main features of classic motor symptoms resulting from dopamine depletion in specific brain regions. However, recent studies have shown that the clinical manifestations of PD are not only related to dopaminergic dysfunction occurring in the substantia nigra, they go beyond that, as the scattered impairment of the central nervous system favors the onset of symptoms considered motor and non-motor, and are characterized by bladder, bowel, sexual and mental dysfunction (1)(2)(3) . These findings redirect the debate on PD pathophysiology and encourage discussion on the impact of these symptoms in the evolution of this disease, considered as progressive and multisystem (1,3) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation